Radiología del género ¿Cuerpos, discursos, poderes? (2018)
The approach of gender studies from a broad perspective, was possible thanks to the analysis and observation of the discursive, symbolic and observable aspects within the social dynamics. Discourse as a form of power over bodies, by creating these networks of truths accepted as possible evidence; An example of this assumption is the statement "He is a boy and his name will be John". This discursive element becomes the truth of the genre for that gender, to which from that moment, it is given some roles according to its genital characteristics; therefore, if this body decides that "Juan" is a discursive element that blurs its gender lines, then a possible "I am not Juan, I am Victoria" would transform the powers that are exercised within the signifier of this body in particular. Is biology a destination according to genitality? What are the signifiers and meanings in this line of thought? These signifiers such as "woman, man, gay, queer, lesbian" would create a meaning according to the cultures that surround these discursive elements, the body would become an element that carries the brands of the genre. Attached to this is the studies and analyzes on the desire of Self for Self, or the Other for Self; making an interpretation to the systems of power exercised by the subject within historical contexts, where it was necessary to portray these aspects of the subject with pride, or to hide them because of the scandalousness of their actions. All this under the constant questioning of heteronormativity (Which are based on a natural reproduction assumption) and patriarchy (How the power exercised by one body over the other).